Kaidah Rasm Dalam Manuskrip Mushaf Al-Qur'an Nagari Tuo Pariangan - Rosa, Elfira; Wendry, Novizal; Hanif, Muhammad (Al-Qudwah, 2023)
West Sumatra is one of the regions that has a substantial collection of Quranic manuscript in the Nusantara. One notable location is Nagari Tuo Pariangan, which houses a number of Quranic manuscript that have been handed down through generations. This article investigates the scriptural aspects (rasm) of the Quranic manuscript preserved by Aswardi, specifically with the identification numbers or codes No. 019 NM and No. 029 NM. The analysis focuses on the origin of the manuscripts and the consistency of the rasm copying in utilizing the script. This research employs a qualitative method, specifically field research, which involves collecting data from the field using observation and documentation techniques on the Quranic manuscript and interviews with the owner or custodian of the manuscripts. The results of this study indicate that the Qur'anic manuscripts from Nagari Tuo Pariangan originate from Surau Tinggi. However, due to the non-functional status of the surau, the manuscripts were brought to a house for personal preservation and became an inherited legacy. Two manuscripts were discovered, both originating from the same source. The identification process of script usage in these manuscripts revealed the utilization of two different scripts: the 'Uthmani script and the Imla'i script. The use of rasm in these manuscripts tends to be inconsistent, as both script types are employed in different verses, with 'Uthmani script used in one verse and Imla'i script in another. This inconsistency in rasm usage indicates that the tradition of copying Qur'anic manuscripts in Nagari Tuo Paringan is motivated by a tradition of writing without incorporating sufficient knowledge of rasm rules. Abstrak: Sumatera Barat merupakan satu daerah yang memiliki koleksi manuskrip mushaf Al-Qur’an cukup banyak di Nusantara. Diantaranya yaitu Nagari Tuo Pariangan yang memiliki sejumlah manuskrip mushaf Al-Qur’an dan telah diwariskan secara turun temurun. Artikel ini bertujuan untuk menginvestigasi aspek rasm manuskrip mushaf Al-Qur’an yang disimpan oleh Aswardi dengan nomor atau kode mushaf dengan No. 019. NM dan No. 029 NM. Analisis difokus pada asal usul manuskrip serta konsistensi penyalin manuskrip dalam menggunakan rasm. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian field research, yaitu mengumpulkan data dari lapangan menggunakan teknik observasi dan dokumentasi terhadap manuskrip mushaf Al-Qur’an, serta wawancara dengan pemiliki atau pemelihara manuskrip. Hasil penelitian ini menunjukkan bahwa manuskrip al-Qur’an Nagari Tuo Pariangan berasal dari Surau Tinggi, namun karena surau yang tidak lagi berfungsi maka naskah tersebut dibawa ke rumah untuk disimpan secara pribadi dan menjadi warisan turun temurun. Ada dua manuskrip yang ditemukan dan berasal dari sumber yang sama. Proses identifikasi penggunaan rasm dalam manuskrip tersebut menghasilkan adanya penggunaan dua rasm yang berbeda dalam penulisannya yaitu rasm ‘uṡmānī dan rasm imlā’i. Penggunaan rasm dalam manuskrip ini cenderung tidak konsisten karena dalam penulisannya menggunakan kedua jenis rasm ini, rasm ‘utṡmānī pada satu ayat dan rasm imlā’i pada ayat lain. Inkonsistensi penggunaan rasm ini menandakan tradisi penyalinan mushaf di Nagari Tuo Paringan tersebut termotivasi dari tradisi tulis menulis yang hidup tanpa diikutsertakan dengan pengetahuan yang cukup tentang kaidah penulisan rasm.